Real-world experience with pembrolizumab toxicities in advanced melanoma patients: a single-center experience in the UK - Alfred CP So; Ruth E Board (Melanoma Management)
Aim: We aimed to characterize the safety profile of pembrolizumab in advanced melanoma patients at our center to better reflect ‘real-world’ data on anti-PD-1 inhibitors. Materials & methods: At our institution, 58 ipilimumab-naive and 30 ipilimumab-treated patients with advanced melanoma who have received pembrolizumab between June 2014 and June 2017 were included for analysis. Results: Incidence of any-grade and grade 3/4 toxicities were 81.8% (n = 72) and 12.5% (n = 11), respectively. The most common side effects were skin-related (61.4%, n = 54) and gastrointestinal-related (51.1%, n = 45) events. In total, 25% of patients required oral steroids to manage immune-related adverse events with a median cumulative prednisolone dose of 683 mg (range: 40–3745 mg). Conclusion: Pembrolizumab is well tolerated in ‘real-world’ patients and severe toxicities can be effectively managed with systemic steroids.